Mineralocorticoid receptor antagonists, a class beyond spironolactone — Focus on the special pharmacologic properties of eplerenone. (1st December 2015) - Seferovic, Petar M.; Pelliccia, Francesco; Zivkovic, Ivana; Ristic, Arsen; Lalic, Nebojsa; Seferovic, Jelena; Simeunovic, Dejan; Milinkovic, Ivan; Rosano, Giuseppe
Abstract: The renin–angiotensin–aldosterone system can be blocked at specific levels by using different classes of pharmacologic agents, including angiotensin-converting-enzyme inhibitors, angiotensin II receptor blockers and mineralocorticoid receptor antagonists. Broad use of the latter, such as spironolactone, has been limited by significant incidence of gynecomastia and other sex-related adverse effects. These problems can be overcome with use of eplerenone, a selective mineralocorticoid receptor antagonist. Eplerenone has been specifically developed to bind selectively to the mineralocorticoid receptors in order to minimize binding to the progesterone and androgen receptors. In the last decade, multiple scientific evidences have been accumulated showing the efficacy and safety of the drug in multiple clinical conditions, including heart failure and arterial hypertension. Eplerenone is generally well tolerated, with the most frequent adverse event being hyperkalemia, with sexual adverse events (i.e. gynecomastia) being more uncommon, due to the selectivity of eplerenone. This review focuses on the pharmacodynamic and pharmacokinetic properties of eplerenone, thus providing the scientific basis to fully understand drug-to-drug interactions, in particular, and its efficacy and tolerability, in general. Noteworthy, the activity of eplerenone in special conditions and different patient populations is summarized.